The Impact of The Ship Spare Parts Supply Delays to The Cancelation of Ships Departure at Humolco Trans Inc Jakarta - Sumali, Bambang; Gunawan, April; Barasa, Larsen (International Review of Management and Marketing, 2018)
The Departure of ships are canceled might be cause of various problems, how ever, if departure of the ships are canceled due to the late of incoming spare parts, it will be bad presedence, since this event will not only make disadvantages to the ships operator but also to the shipper where as the cargo is carried by that ships. The 22 times (66%) delay of ship departure from 36 voyage have happened to the ships which is operated by Humolco Trans Inc- Jakarta. The data showed that the canceled occured because of the delay of the existence of spare parts which are ordered by the ships. This events show that miss management of spare parts have happend. That could be happened at ships or operators management, or the suplliers which is without realized will breach and disturbing other activities regarding the operation of the ships including the images of the shippers. The result of this research shows that there is strong positif correlation (94%) between the delay of spare parts existence and the cancelled of ship voyages, there are 89 % the influence of the spare parts existence to the cancelled of ships departures. Therefore, to the future this condition should be able to overcome by those who involved in the management of spare parts. Keywords: spare parts, ships, departure cancelled JEL Clasifications: L62, R41, R42 DOI: https://doi.org/10.32479/irmm.7321